ANALYSIS OF THE STATE OF HANDLING WASTES OF OIL AND GAS INDUSTRY AND WAY OF THEIR UTILIZATION - Шкіца, Л. Є.; Троценко, А. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the article the results of analytical researches in relation to the state of handling wastes of oil and gas industry and ways of their utilization.